Analysis of the Effectiveness of Mosque Financial Management in Improving the Welfare of the Mega Rezky Mosque Congregation in Gowa Regency - Lutfi Andi Abrar; Nur Indah Cahyani; Nur Isnaini Syaifullah; Bayu Irsandi Putra; Imel Rahmadani; Radia; Muttiarni (JEKAMI Journal of Accounting, 2024)
With the increasing number of mosque construction and the number of Muslim population in Indonesia, the opportunity to optimize the function of mosques through effective financial management is also increasing. The command to prosper mosques is clearly stated in the Qur'an and As- Sunnah . Considering the significant positive impact on society, efforts to prosper mosques require planned and structured financial management. Good mosque financial management includes not only recording and reporting transactions, but also budget planning, cash management, and appropriate allocation of funds for various mosque programs and activities. The research method used in this research is based on a literature review of relevant previous research and various scientific journals. By referring to previous research, this research seeks to adapt and develop a methodology that has been proven effective. This approach was taken to ensure the validity and reliability of the data produced, so that the method used has a strong basis and has been scientifically tested . As for the fact that there are still many mosque administrators who do not understand the social realities in their mosque environment for various reasons, the administrators are so busy that they do not have time to pay attention to the movement of people's lives, so it is necessary to think about it so that whoever becomes the financial manager of the mosque is not from a group whose activity schedule is too busy so that their main duties as DKM are neglected. The author suggests that training be carried out for the management of the Mega Rezky Mosque, especially the mosque treasurer, regarding professional mosque management. This training aims to increase the knowledge and ability of administrators in preparing mosque financial reports in accordance with applicable accounting principles. In this way, it is hoped that mosque financial management can be carried out more effectively, transparently and accountably